Digital PR - Whatmough, Danny (PRCA practice guides, 2018)
Digital changes everything. That's a truth that has played out across industries the world over. And PR is a perfect example of an industry that has been forced to transform. Across every PR discipline, from media relations and content creation through to social media and influencer marketing, digital has changed traditional PR techniques and ushered in a whole new wave of specialisms that previously did not exist. This book acts as a guide to this era of transformation. It's a manual that summaries the trends affecting our industry. It examines the techniques that have changed and also investigates some of the new approaches that are starting to emerge. It poses the questions that modern PR practitioners need to ask, whether working in-house or in an agency, and will be equally relevant for those studying PR or coming into the industry as it will those who are hardened professionals facing a future that looks significantly different to the tried and tested approaches of the past. This is a book about opportunity. A book that shines a light on how adoption of data, audience planning and creativity, seen through a digital lens, can transform an industry, making it more relevant and necessary that ever before. It's a celebration of the power of earned media in a world where we are, as consumers of media, increasingly shunning interruptive marketing and looking for connection and true engagement.